Exploring MAO inhibitory activity of 5-hydroxy regioisomers of hispidol’s analogs leads to identification of novel highly selective MAO-B open-conformation inhibitors - Ahmed H. E. Hassan; Rium Kim; Sung Yeun Yoo; Lamiaa O. El-Halaby; Selwan M. El-Sayed; Minji Kim; Hyeon Jeong Kim; Ki Duk Park; Jaehoon Sim; Yong Sup Lee (Molecular Diversity, 2026)

Angiopoietin-2 binds to FGFR2, inhibits FGF-FGFR2 signaling, and delays cutaneous wound healing by inhibiting wound angiogenesis - Minji Sim; Hidetaka Ohnuki; Stewart Durell; Haydar Bulut; Yuyi Wang; Marzena Dyba; Sergey G. Tarasov; Lisa M. Jenkins; Giovanna Tosato (Angiogenesis, 2025)
Wound healing is an essential repair process, and impaired wound healing is a common and sometimes debilitating medical problem. Despite advances in wound healing approaches, optimal management strategies are lacking, partly due to an incomplete understanding of the complex pathophysiology of this process. Here we show that Ang2, a previously known ligand for the Tie2 receptor, also binds to fibroblast growth factor receptor 2 (FGFR2) independently of Tie2 and attenuates FGF/FGFR2 signaling in endothelial cells. Functionally, Ang2 inhibits endothelial cell migration induced by FGF. In mouse, topical Ang2 delays the healing of skin wounds, associated with reduced wound angiogenesis and recruitment of mesenchymal-type cells. Additionally, topical AMG386, a blocker of Ang1/Ang2 binding to Tie2 and systemic REGN910, a blocker of Ang2 binding to Tie2, accelerate wound repair, associated with increased wound angiogenesis and recruitment of inflammatory cells. These results identify the tyrosine kinase FGFR2 as a previously unrecognized Ang2 receptor, explaining some of the context-dependent functions of Ang2 in endothelial cells. Since Ang2 is induced in cutaneous wounds and endogenous FGF/FGFR2 is essential for wound repair, Ang2 blockade holds promise as a new evidence-based therapeutic option to promote wound repair.

Monkeypox virus detection using wastewater surveillance during the Mpox outbreak in the Republic of Korea - Jeong Hyun Lee; Gyuri Sim; Hye Jin Park; Minji Lee; Hwajung Yi; Yoon-Seok Chung (Journal of Environmental Chemical Engineering, 2024)

RNase III Controls mltD mRNA Degradation in Escherichia coli - Boram Lim; Sangmi Ahn; Minji Sim; Kangseok Lee (Current Microbiology, 2014)